Bad Girls at Samarcand : Sexuality and Sterilization in a Southern Juvenile Reformatory - Zipf, Karin L., 1968- (Book collections on Project MUSE., 2016)
North Carolina's forced sterilization of more than 2,000 women and girls is among the many horrors that accompanied the rise of the eugenics movement in the early twentieth century. This extreme measure, inflicted with impunity from 1929 to 1950, reflects how pseudoscience justified widespread gender, race, and class discrimination in the Jim Crow south. In 'Bag girls at Samarcand' Karin L. Zipf dissects a dark episode in North Carolina's eugenics campaign through a detailed study of the State Home and Industrial School in Eagle Springs, referred to as Samarcand Manor, and the schools infamous 1931 arson case. The people and events surroundign both the institution and the court case sparked a public debate about womanhood, the nature of contemporary science and medicine, and the role of the juvenile justice system that resonated throughout the succeeding decades. Designed to reform and educated unwed poor white girls who were suspected of deviant behavior or victims of sexual abuse, Samarcand Manor allowed for strict disciplinary measures--including corporal punishment--in an attempt to instill Victorian ideals of female purity. The harsh treatment fostered a hostile environment and tensions boiled over when several girls set Samarcand on fire, destroying two residence halls. Zipf argues that the subsequent arson trial, which carried the possibility of the death penalty, represented an important turning point in the public characterizations of poor white women; aided by the lobbying efforts of eugenics advocates, the trial helped usher in dramatic policy changes, including the forced sterilization of female juvenile delinquents.